Mimicry in child marriage in the novel Yuni by Ade Ubaidil - Maman Qomaruzzaman (Privietlab, 2026)
This study examines the practice of mimicry in the phenomenon of child marriage as represented in the novel Yuni by Ade Ubaidil. Mimicry is understood as a postcolonial concept proposed by Homi K. Bhabha, referring to the partial imitation of dominant values, norms, and discourses that produces ambivalence and identity negotiation. The novel Yuni portrays the social realities of rural Indonesian society, where child marriage is normalized through cultural traditions, religious interpretations, and economic pressures. This research aims to reveal how the characters in the novel perform mimicry toward patriarchal values and moral discourses legitimized by social authorities, and how such mimicry functions as a form of apparent compliance, survival strategy, or subtle resistance. This study employs a qualitative descriptive method using a postcolonial theoretical approach, particularly Bhabha’s concept of mimicry. The data consist of narrative descriptions, dialogues, and character portrayals related to child marriage and female identity construction. The analysis is conducted through critical and interpretative textual reading. The findings indicate that mimicry in Yuni not only reinforces unequal power relations but also creates spaces of ambivalence that allow the emergence of critical awareness toward gender injustice. This study contributes to the understanding of power, identity, and resistance in contemporary Indonesian literary studies.